Prefrontal cortex function and gait alterations during single- and dual-task walking in knee osteoarthritis - Soyoung Lee; Ehyun Kim; Dilinazi Duolikun; Baekdong Cha; Claudio L. Ferre; Meryem Yücel; Deepak Kumar (PLoS ONE, 2025)
Over-recruitment of the prefrontal cortex (PFC) during complex walking conditions may reflect altered motor and cognitive performance in people with knee osteoarthritis (OA). Our objectives were (1) to assess PFC activation, and motor and cognitive performance, during single- and dual-task walking in people with knee OA and (2) to examine the association of PFC activation with the performance. Forty-eight people with symptomatic knee OA completed three tasks, (1) single-task walking (STW) (2) subtraction by 7 from a 3-digit number (S7), and (3) dual-task walking (DTW), a combination of STW and S7. Oxygenated hemoglobin concentration changes (ΔHbO2) in bilateral prefrontal cortex (PFC) were assessed using functional Near-Infrared Spectroscopy. Motor performance outcomes included gait speed, step duration variability, and stride length variability. Cognitive performance was assessed as the correct response rate during S7. We used repeated measures ANCOVA to compare the outcomes by tasks. Correlation and multiple linear regression analyses were used to determine the association between PFC activation and performance outcomes. PFC activation was higher during STW and DTW compared to S7 but not significantly different between STW and DTW. People with knee OA walked slower (d = 0.63) and had higher variability in step duration (d = 0.45) and stride length (d = 0.37) during DTW compared to STW. Greater activation in right ventrolateral PFC (R2 = 0.15) and left dorsomedial PFC (R2 = 0.12) were associated with lower step duration variability. When walking is challenged with a cognitive task, people with knee OA show deterioration of gait performance and no change in PFC activation.